Electrochemical migration of silver in electronics applications - Mena, Marie Stephanie S. (2009)
Silver (Ag) filler is the most attractive choice among all the conductive fillers or die attached material because of its balanced properties and relatively low cost. However, a major problem of silver is that electrochemically migrates in the presence of moisture and applied bias in IN microelectronic devices, silver migration usually occurs between adjacent conductors/electrodes, which leads to the formation of dendrites and eventually results in short-circuit failure. In order to assess the reliability of these conductive fillers, an investigation for two types of fillers was done using the water drop test, in which % relative humidity(%RH) was 100% at room temperature (25ºC), and using a 1000-hour temperature-humidity-bias (THB) test with 85ºC and 85%RH conditions. Four different bias voltages and six different distance spacings were used for each of the two fillers. Both dendrites and clouds were observed as a result of electrochemical migration of silver. Water drop test results revealed that increasing bias voltage and decreasing distance spacing causes migration to occur faster thus resulting the time to fail (TTF) to be rapid/short. However, the voltage requirement for Ag migration to begin is higher for the high resistivity epoxy, as a consequence of the resistivity difference. A good fir was obtained between the data and the Hornung equation which described a linear relationship between TTF and the electric field ap[plied. An estimated activation energy of 0.2 eV suggests diffusion of Ag+ ions as the rate determining step. A linearly increasing dendrite growth further suggests that migration is controlled by field-assisted diffusion. A design rule for the prevention of Ag migration was also obtained to have an electric field value of about 1 volt/mm. Above this value, migration will occur. THB testing resulted to negligible failure points since water was not able to condense on the surface.